Digital Marketing Strategy of Small and Medium Enterprises for Snack in Bogor City - Ratnadianti, Aulia; Fahmi, Idqan; Hannan, Sufrin (School of Business, Bogor Agricultural University (SB-IPB), 2020)
Snack MSME (Micro, Small & Medium Enterprises) is one of the business unit categories that has great potential to be developed at this moment. This study aimed to formulate digital marketing alternative strategies for snack MSME in Bogor. This study began with the analysis of respondent characteristics, both for MSME respondents and consumer respondents. The next step was an analysis of marketing strategies of snack MSME and consumer online purchasing behavior pattern This study also analyzed consumer satisfaction level to MSME digital marketing performance with Importance Performance Analysis, while also mapping consumer preferences based on digital marketing mix. The final step was to develop a digital marketing strategy based on the 4C marketing mix. This research resulted in eleven digital marketing strategies, which were increasing the durability of snack food products, providing a variety of diverse product flavors, designing attractive packaging and brand appearance, providing information on products nutritional value, determining affordable prices, utilizing appropriate information media, choosing appropriate promotional media, creating attractive promotions for consumers, displaying consumer testimonials, displaying honest pictures and product descriptions, and providing various types of the payment instrument. Keywords: consumer online snack purchasing behavior, marketing mix 4C, snack MSME, digital marketing strategy